A Cross-Linked Interconnecting Layer Enabling Reliable and Reproducible Solution-Processing of Organic Tandem Solar Cells - Liu, Chao; Du, Xiaoyan; Gao, Shuai; Classen, Andrej; Osvet, Andres; He, Yakun; Mayrhofer, Karl; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2020)
The performance of tandem organic solar cells (OSCs) is directly related to the functionality and reliability of the interconnecting layer (ICL). However, it is a challenge to develop a fully functional ICL for reliable and reproducible fabrication of solution-processed tandem OSCs with minimized optical and electrical losses, in particular for being compatible with various state-of-the-art photoactive materials. Although various ICLs have been developed to realize tandem OSCs with impressively high performance, their reliability, reproducibility, and generic applicability are rarely analyzed and reported so far, which restricts the progress and widespread adoption of tandem OSCs. In this work, a robust and fully functional ICL is developed by incorporating a hydrolyzed silane crosslinker, (3-glycidyloxypropyl)trimethoxysilane (GOPS), into poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and its functionality for reliable and reproducible fabrication of tandem OSCs based on various photoactive materials is validated. The cross-linked ICL can successfully protect the bottom active layer against penetration of high boiling point solvents during device fabrication, which widely broadens the solvent selection for processing photoactive materials with high quality and reliability, providing a great opportunity to continuously develop the tandem OSCs towards future large-scale production and commercialization.
CRIS-Team Scopus Importer:2020-02-25
Keywords: (3-glycidyloxypropyl)trimethoxysilane; cross-linking; interconnecting layer; organic tandem solar cells; solution-processing

Electrical-Field-Driven Tunable Spectral Responses in a Broadband-Absorbing Perovskite Photodiode. - Tang, Xiaofeng; Matt, Gebhard; Gao, Shuai; Gu, Ening; Almora, Osbel; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Controllably manipulating the spectral response of broadband-absorbing semiconductors is crucial for developing wavelength-selective optoelectronic devices. In this article, we report for the first time, the bias-dependent spectral responses for a metal-halide perovskite photodiode. Tunable external quantum efficiencies in the short- and long-wavelength regimes, and the full spectral range (ca. 300-800 nm) are observed when the device is operated under short-circuit, and forward and reverse bias conditions, respectively. This observation is understood by the interplay of wavelength-dependent penetration depth and barrier formation within the photodiode device stack. The general applicability of this concept is confirmed by a systematic study on a series of mixed-halide perovskite devices. These results suggest that the proposed concept allows as a promising platform and should inspire further exploration of multispectral responsive optoelectronic devices.
Keywords: perovskite; optoelectronics; electrodeposition; mixed-halide perovskite; external quantum efficiency

Time-Resolved Analysis of Dielectric Mirrors for Vapor Sensing - Gao, Shuai; Tang, Xiaofeng; Langner, Stefan; Osvet, Andres; Harreiß, Christina; Barr, Maissa; Spiecker, Erdmann; Bachmann, Julien; Brabec, Christoph; Forberich, Karen (ACS Applied Materials and Interfaces, 2018)
Dielectric mirrors based on bilayers of polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SEBS) and poly(vinyl alcohol) (PVA)-zirconium dioxide (ZrO2) nanocomposites are fabricated for vapor sensing. When exposed to specific solvent vapor, the layers of dielectric mirrors can gradually swell and cause a red-shift of the reflection band. Because PVA solely responds to water and SEBS is sensitive to several different types of organic solvents, the mirrors can respond to a large variety of solvents. The dual-functional hydrophilic ZrO2 nanoparticles are introduced to not only enlarge the refractive index contrast but also increase the permeability. Time-resolved measurements show that mirrors with nanoparticles have a significantly faster response than those without nanoparticles. Moreover, the dependence on relative humidity is studied for representative solvents, and several types of solvents are selected to show the dependence on the solvent-polymer interaction parameters at typical relative humidity, which allows one to predict the responsivity and selectivity of the sensors. © 2018 American Chemical Societ
Keywords: dielectric mirrors; distributed Bragg reflectors; vapor sensing; fully printed; time-resolved analysis